Pengaruh Perlakuan Alkali (NaOH) Terhadap Morfologi dan Kekuatan Tarik Serat Mendong - Witono, Kris; Irawan, Yudy Surya; Soenoko, Rudy; Suryanto, Heru (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2013)
Chemical modification on fiber by using Natrium Hydroxide (NaOH) solution directly affect to the fiber structure such as changing the chemical composition of the fiber and improve the performance of natural fiber as the composite reinforcement. The purpose of this study is to inverstigate the effects of NaOH solution to the tensile strength and the mofology of Mendong fiber. The concentration of NaOH solution were 2,5% v/v; 5% v/v; dan 7,5% v/v on this experiment. Mendong fiber was soaked for 2, 4 and 6 hours in NaOH solution. The temperature on this study was 26 o C. The tensile strength of Mendong fiber was increased by increasing the NaOH solution concentration and duration of soaking after exceed the concentration of NaOH solution and duration of soaking the tensile strength would be decreased. The highest tensile strength was 497,34 MPa with NaOH solution concentration 5% v/v and the duration of soaking, 2 hours. The roughness of Mendong fiber by soaking in NaOH solution was higher than without soaking in NaOH solution. Soaking on the highest concentration of NaOH solution caused the highest roughness.Keywords: NaOH solution, Mendong fiber, tensile strength, roughness.